(3GdbGfhf aj GdfMhs - (3YjSi Hf YHO GdYRjR Hf jddHNJ GdLRhdj GdHQHQj GdeQGcTj, CHh ehSi,J (B607 (3g` s
(3ChdgG (B:s
(3GdcdGe gh GddaX GdeQcH GdebjO HGdhVY GdGSe cd cdeI OdJ Ydi eYfi s
(3BNQgG (B:s
(3gi GSe heYfGgG MbkG hbGd CHh eMeO GdOdjd Ydi GfgG GSe GdJfhjf Je cJGH GdbGfhf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B104 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B27s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1800s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI (B(139) s
Keywords: (3GdfMhs